The Influence of Leadership Style and Organizational Culture on Employee Performance, Mediated by Job Satisfaction - Salim, Aji Nur; Liana, Lie (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of leadership style and organizational culture on employee performance mediated by job satisfaction. The population is 803 employees of Community Health Centers in Wonosobo Regency. The number of samples was calculated using the Slovin formula and obtained a sample size of 100 employees. Sampling used a purposive sampling technique with the criteria of employees with permanent employee status (PNS, PPPK and BLUD) and a minimum education of high school. Data were processed using SPSS software version 27. Data analysis techniques include respondent descriptions, variable descriptions, validity tests, reliability tests, F tests, R2 tests, t tests, and Sobel Tests. The results of the study stated that leadership style does not affect job satisfaction, organizational culture has a positive effect on job satisfaction, leadership style has a negative effect on employee performance, organizational culture has a positive effect on employee performance, and job satisfaction has a positive effect on employee performance, job satisfaction does not mediate the effect of leadership style on employee performance, and job satisfaction mediates the effect of organizational culture on employee performance.